2013
DOI: 10.1177/1071100712475062
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Excision of a Symptomatic Os Trigonum in a Lateral Decubitus Position

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…Average time to return to sports or activities was 5.9 weeks to 5.8 months. 23,[60][61][62][63]65,66,[70][71][72] Open excision of the os trigonum through PM or PL approaches were effective and safe in the patients with os trigonum syndrome. 29,73 Previous studies reported significant improvement of AOFAS scores, and average AOFAS scores were 87.6 to 100.0 points at the final postoperative visit.…”
Section: Clinical Outcomes Os Trigonummentioning
confidence: 98%
See 2 more Smart Citations
“…Average time to return to sports or activities was 5.9 weeks to 5.8 months. 23,[60][61][62][63]65,66,[70][71][72] Open excision of the os trigonum through PM or PL approaches were effective and safe in the patients with os trigonum syndrome. 29,73 Previous studies reported significant improvement of AOFAS scores, and average AOFAS scores were 87.6 to 100.0 points at the final postoperative visit.…”
Section: Clinical Outcomes Os Trigonummentioning
confidence: 98%
“…29 In posterior arthroscopic debridement using the supine position, a potential hazard is injury to the calcaneofibular ligament or peroneal tendons while making the centrolateral portal. 66 Superficial wound infection was reported in 3.3% to 6.7% 29,62 and deep wound infection in 3.3% from the arthroscopic approach, 62 whereas only superficial wound infection was reported in 2.4% from the open approach. Ankle stiffness was reported in 6.7% and triggering of the hallux in 3.7% from the arthroscopic approach; there are no such reports in series involving the open approach.…”
Section: Complications and Concerns Complicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…The posterior process of the talus, also known as Stieda's process, can be associated with the syndrome of posterior impingement of the talus, especially in athletes and ballet dancers (Bizarro, ; Russell et al , ). Its clinical management requires arthroscopic surgery, in which Stieda's process is removed (Park et al , ). Also described in the literature is the existence of an accessory bone, the os trigonum, which is associated with the posterior process of the talus and has no defined function.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been frequently associated with chronic complaints related to plantar flexion mechanisms (Bizarro, ). In the symptomatic posterior ankle impingement syndrome, the removal of these structures has been described and proposed for pain management (Park et al , ; Russell et al , ). The orthopaedic community assumes that the arthroscopic excision of these structures is not associated with significant morbidity (Chao, ).…”
Section: Introductionmentioning
confidence: 99%